Histopathological Changes in the Gill and Intestine Tissues of Fish from Pichavaram Mangroves, South east Coast of India - Annamalai, Anbu; Rajendran, Narendran; Kaliyappan, Manoj; Arunachalam, Manimekalan (Discoveries in Agriculture and Food Sciences, 2023)
A study was conducted to analysis the Histopathological Changes in the Gill and Intestine Tissues of Mystus gulio and Mugil cephalus from Pichavaram Mangroves for different seasons. The maximum overall metal concentrations of Iron (Fe) recorded in the gills of M. cephalus was found to be maximum in S2 as 48.41±0.72 mg/l, copper (Cu) is maximum at station 6 as 0.52±0.02 mg/l, chromium (Cr) accumulation in the gills of M. gulio was highest in S5 as 5.23±0.05 mg/l, the highest lead (Pb) accumulation in the gills of M. gulio was found to be maximum in S6 as 0.71±0.03 mg/l. Likewise, the highest Iron (Fe) accumulation in the kidney of M. gulio was found to be maximum in S2 as 36.13±0.41 mg/l followed by copper (Cu) in (S6) 0.41±0.02 mg/l, Chromium (Cr) in (S6) records at 2.98±0.06 mg/l and by lead (Pb) maximum in S5 0.64±0.06 mg/l. The highest Iron (Fe) accumulation is found in the liver of M. gulio in S2 as 29.14±0.34 mg/l, followed by copper (Cu) in (S3) 0.32±0.01 mg/l, Chromium (Cr) in (S6 and S1) as 2.98±0.06 & 2.98±0.03 mg/l respectively and in lead (Pb) the highest concentration is recorded at S6 1.10±0.06 mg/l. The highest Iron (Fe) accumulation is found in the intestine of M. gulio was found to be maximum in S6 as 29.11±0.44 mg/l and by copper (Cu) in (S6) 1.61±0.01 mg/l and chromium (Cr) in (S5) as 2.43±0.03 mg/l and in lead (Pb) at S6 1.74±0.03 mg/l. The highest Iron (Fe) accumulation is found in the muscle of M. gulio in S1 as 14.03±0.37 mg/l, followed by copper (Cu) in (S2) 1.83±0.06 mg/l, Chromium (Cr) in (S6) as 2.63±0.03 mg/l and in lead (Pb) the maximum in S6 1.52±0.03 mg/l.